PERANCANGAN ANTARMUKA SISTEM MONITORING PERTANIAN UNTUK PENGGUNA NON-TEKNIS DENGAN PENDEKATAN BERORIENTASI OBJECT - Arif Ginanjar; Aditya Tri Prabowo; Faiq Irfandi Salim; Ilham Albana (CV. Denasya Smart Publisher, 2026)
The agricultural sector in Indonesia faces significant challenges in adopting digital technology due to user interface designs that are often too technical and complex for the general public. Although IoT-based monitoring systems are increasingly being developed, the presentation of raw data and complex graphs often leads to misinterpretation of information by non-technical users. This research aims to design an agricultural monitoring system interface specifically tailored for users without an IT background, with a focus on visual clarity and ease of interaction. Development was conducted using an Object-Oriented approach, leveraging the Unified Modeling Language (UML) to model user interaction requirements through use case, class, and sequence diagrams. The research resulted in a modern interface architecture that integrates intuitive visual metaphors, such as a 2D thermometer indicator for temperature and a water droplet icon for humidity, supported by a color-based warning system. The findings indicate that by simplifying data presentation and using familiar visual representations, the system can bridge the digital literacy gap. In conclusion, user-centered interface design significantly enhances the effectiveness of environmental parameter monitoring and promotes the adoption of sustainable smart farming technology among non-technical farm managers.